Maturation of P300 amplitude and short-term learning as reflected by P300 habituation between trial blocks in children - Pfüller, Ute; Oelkers-Ax, Rieke; Gmehlin, Dennis; Parzer, Peter; Roesch-Ely, Daniela; Weisbrod, Matthias; Bender, Stephan (International journal of psychophysiology, 2011)
Although numerous studies concerning P300 have been reported in adults, few have focused on the normal development of children, particularly in relation to habituation. The aim of this study was to investigate maturation of the P300 component and its habituation (short-term automatic learning) in a sample of healthy children and adolescents. Four models of maturation of the P300 (linear, quadratic or two different linear regressions for the pre-pubertal and pubertal age groups as well as age-inverse) were applied and compared, in order to find the most adequate model according to the Bayesian Information Criterion. A visual oddball paradigm was presented to 81 healthy children and adolescents aged 6-18 years. Three blocks, each with 200 trials were recorded to assess between-block habituation. The data was best fitted to (a) an age-inverse relation between P300 latency and age, and (b) a linear relationship between P300 amplitude and age. An age-dependent effect of habituation was detected in the P300 amplitude, where a considerable amplitude decline was found in the younger children and no significant change for adolescents. Our results support the hypothesis that younger children show stronger habituation effects because they activate a larger neuronal pool from which unnecessary neurons can be excluded during short-term learning. In contrast, in adolescents, these neurons may have already been eliminated as a consequence of pruning, thus reducing habituation effects. Future studies are required to test this hypothesis because our data do not permit alternative explanations to be discarded.